2019
DOI: 10.1093/jscr/rjz283
|View full text |Cite
|
Sign up to set email alerts
|

Spinal extradural arachnoid cyst in a child—a case report

Abstract: Extradural spinal arachnoid cysts are rare lesions. They frequently communicate with the subarachnoid space through a defect in the dura. Symptoms result from compression of the spinal cord or nerve roots. The treatment of choice is complete surgical excision. We report the case of a 12-year-old girl with extradural spinal arachnoid cyst who had complete surgical excision with good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The atrophy and decreased extremity weakness can cause abnormal or imbalance body posture, as we found in our patient. 5,7, 8 We found additional clinical findings in our patients were the presence of pathological reflexes such as Hoffman Tromner reflex, Babinski reflex, Chaddock disturbance. 5, 9 In our case report's patient, we cannot evaluate the sensory function because the patient was not cooperative.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The atrophy and decreased extremity weakness can cause abnormal or imbalance body posture, as we found in our patient. 5,7, 8 We found additional clinical findings in our patients were the presence of pathological reflexes such as Hoffman Tromner reflex, Babinski reflex, Chaddock disturbance. 5, 9 In our case report's patient, we cannot evaluate the sensory function because the patient was not cooperative.…”
Section: Discussionsupporting
confidence: 52%
“…The recurrence rate was 37% in the series by Oyemolade TA et al, and the interval between the initial surgery and recurrence was 4-14 years. 8 In contrast, Liu JK et al, reported no recurrence in any of their eight patients during a mean period of 38 months. 7 Nabors et al have reported excellent results initially, with some patients suffering long-term neurological deterioration without evidence of cyst recurrence.…”
Section: Case Reportmentioning
confidence: 87%
“…[ 6 , 8 ] Lesions are more commonly located dorsally resulting in displacement of the spinal cord anteriorly. [ 3 , 8 , 13 , 19 ] As in this case, SEACs commonly extend over several spinal segments, ranging between 2 and 13, with a mean of 5.04 vertebrae. [ 2 , 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…They comprise only about 1–3% of all spinal masses. [ 13 , 19 ] Along the length of the spinal cord, spinal arachnoid cysts could be intradural, extradural, or perineural in location. [ 8 ] Two studies that analyzed 35 patients with spinal arachnoid cysts demonstrated that intradural arachnoid cysts are more common than extradural arachnoid cysts, with the prevalence of each ranging between 50–54% and 27–38%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was always found that the SEACs had a pedicle linking with dura mater [ 4 , 28 ]. In our cases of total cyst excision, most cysts were round on both blind ends, and the cysts could be removed en bloc after wholly separating from the dura [ 9 , 13 , 28 , 29 ] ( Fig. 5 A and B).…”
Section: Discussionmentioning
confidence: 99%